'I decided not to go into surgery due to dress code': a cross-sectional study within the UK investigating experiences of female Muslim medical health professionals on bare below the elbows (BBE) policy and wearing headscarves (hijabs) in theatre. Issue 3 (20th March 2019) - Malik, Abida; Qureshi, Hafsah; Abdul-Razakq, Humayra; Yaqoob, Zahra; Javaid, Fatima Zahra; Esmail, Faatima; Wiley, Emma; Latif, Asam
Abstract : Objectives: The objective of this study is to explore the impact of workplace dress code policies and guidance that may influence inclusivity and opportunities in the workplace. Design: Quantitative, self-completion cross-sectional survey. Setting: British Islamic Medical Association conference. Participants: Eighty-four female medical healthcare professionals with a range of ethnicities and wide geographical coverage. Primary and secondary outcome measures: The study reports on the experiences of female Muslim healthcare professions wearing the headscarf in theatre and their views of the bare below the elbows (BBE) policy. Percentage of positive answers and their respective 95% CIs are calculated. Results: The majority of participants agreed that wearing the headscarf was important for themselves and their religious beliefs (94.1%), yet over half (51.5%) experienced problems trying to wear a headscarf in theatre; some women felt embarrassed (23.4%), anxious (37.1%) and bullied (36.5%). A variety of different methods in head covering in operating theatres were identified. The majority of respondents (56.3%) felt their religious requirement to cover their arms was not respected by their trust, with nearly three-quarters (74.1%) of respondents not happy with their trust's BBE uniform policy alternative. Dissatisfaction with the current practice of headscarves in theatre and BBE policy was highlighted, with some respondents preferring to specialise as GPs rather than in hospital medicine because of dress code matters. The hijab prototype proposed by the research team also received a positive response (98.7%). Conclusions: Our study suggests that female Muslims working in the National Health Service (NHS) reported experiencing challenges when wearing the headscarf in theatre and with BBE policy. The NHS needs to make its position clear to avoid variations in individual trust interpretation of dress code policies. This illustrates a wider issue of how policies can be at odds with personal beliefs which may contribute to a reduction in workforce diversity.